Work-related factors and hair cortisol concentrations among men and women in emergency medical services in Sweden - Anna M. Johnsen; Elvar Theodorsson; Anders Broström; Petra Wagman; Eleonor I. Fransson (Scientific Reports, 2023)
Abstract Ambulance personnel in emergency medical services are exposed to physical demands and stress during work, and an increased prevalence of ill health has been observed in this group. The aim was to compare hair cortisol concentration (HCC) among Swedish ambulance personnel with HCC in a population-based reference sample, to analyse differences between women and men, and differences due to work-related factors. Samples of hair 1 cm closest to the skin (5–10 mg) were collected and analysed for cortisol by radioimmunoassay. Moreover, the participants responded to a questionnaire regarding their work environment. The HCC among the ambulance personnel did not differ from the HCC in the population-based reference sample (median 19.2 vs. 22.2 pg/mg, p = 0.319), nor were there statistically significant differences between women and men. Furthermore, no associations were found between HCC and physical and psychosocial work demands, work stress, or rest and recovery from work. However, occupational balance was positively correlated with HCC (rp = 0.240; p = 0.044). The association remained statistically significant after adjustment for sex, age, hair bleaching, and corticosteroid treatment in a linear regression model. This study adds knowledge regarding HCC among ambulance personnel, and thus contributes to the overall picture of work environment and health for this group.